2013
DOI: 10.12691/ajcmr-1-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Virological Response of Viral Hepatitis C to Combination Therapy with Pegylated Interferon Plus Ribavirin

Abstract: A combination therapy with pegylated interferon (PEG-IFN) plus ribavirin (RBV) has made it possible to achieve a sustained virological response (SVR) of 50% in refractory cases with genotype 1b and high levels of plasma HCVRNA. Several factors including virus mutation and host factors such as age, gender, fibrosis of the liver, lipid metabolism, innate immunity, and single nucleotide polymorphism (SNPs) are reported to be correlated to therapeutic effects. However, it is difficult to determine which factor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
2
1
Order By: Relevance
“…This finding was also in agreement with Rezik, (2012) who found that more than two thirds of patients were male .According Mohsen et al, (2011) they reported that, the incidence of chronic hepatitis C receiving combination therapy were higher in men rather than woman. On the other hand, this finding disagreed with Faisal, et al, (2013) who reported that, the incidence of chronic hepatitis C among hepatitis receiving combination therapy was similar for men and women.…”
Section: Discussioncontrasting
confidence: 79%
“…This finding was also in agreement with Rezik, (2012) who found that more than two thirds of patients were male .According Mohsen et al, (2011) they reported that, the incidence of chronic hepatitis C receiving combination therapy were higher in men rather than woman. On the other hand, this finding disagreed with Faisal, et al, (2013) who reported that, the incidence of chronic hepatitis C among hepatitis receiving combination therapy was similar for men and women.…”
Section: Discussioncontrasting
confidence: 79%
“…Also this finding were in agreement with the results of Faisal et al [17] and Nattermann et al [18] who reported that a higher level of IL-6 is significantly associated with SVR compared with a lower level. In contrast, Cotler et al [19] reported that there was no significant difference in basal IL-6 levels between the groups of responders and non-responders to IFN therapy.…”
supporting
confidence: 93%
“…This agrees with the study which was done by Cotler [35] who stated that there was no correlation between SVR and baseline of serum levels of interleukin-6. In contrast to, Nattermann [36] and Faisal [37] who stated that serum level of IL-6 was higher in group who achieved SVR than those who did not and this could be used as a response predictor.…”
Section: Discussionmentioning
confidence: 88%